ChemInform Abstract: Novel Dihydropyrazines and Their Double ortho‐Annulation to Hexaazapentacenes. Issue 52 (29th December 2014) - Strathausen, Rainer; Beckert, Rainer; Fleischhauer, Jan; Mueller, Dirk; Goerls, Helmar
Abstract Simple cycloacylation of oxalic amidines (I) with bis‐imidoyl chlorides (II) gives dihydropyrazine derivatives (III), which provide access to hexaazapentacene derivatives via a double intramolecular ring closure reaction.